Constrained variational approach for energy derivatives in Intermediate hamiltonian fock-space coupled-cluster theory - Ghosh, Aryya; Gupta, Jitendra; Pal, Sourav; Vaval, Nayana (Chemical Physics, 2012)
Fock-space multi-reference coupled cluster theory is an efficient method for electronic structure of nearly degenerate cases. However, it suffers from the intruder state problem for large model space. The intermediate Hamiltonian formulation eliminates intruder state problem and helps in the convergence of equations. In this paper we have implemented intermediate Hamiltonian approach in Fock-space coupled cluster method for the response properties. We test our method for the dipole moments of doublet radicals. We report dipole moments of CN, SF and NS radicals. (C) 2011 Elsevier B. V. All rights reserved.
Keywords: Constrained variational approach; Fock-space multi-reference coupled cluster; Intermediate Hamiltonian theory; Response approach

Excited state geometry optimisation using fock-space multi-reference coupled cluster method - Dutta, Achintya Kumar; Bhattacharya, Sumantra (Molecular Physics, 2014)
The Fock-space multi-reference coupled cluster method is used for the geometry optimisation of the low-lying excited states of the molecules. Molecular geometries of the carbon monohydride cation (CH)(+), water (H2O), ozone (O-3) and formaldehyde (HCHO) in their low-lying excited states are optimised. Excited state gradients are calculated using finite field multi-reference coupled cluster method. We compare our results with other theoretical and/or experimental results, wherever available.
Keywords: adiabatic excitation energy; excited state; Fock-space multi-reference coupled cluster; geometry optimisation; numerical derivative